Reframing workplace safety, wellbeing, and performance among operating room nurses in contemporary healthcare systems - Liying Zhang; Yun Feng; Dan Li; Dongfang Liu (Frontiers in Public Health, 2026)
Operating rooms are complex, high-risk, and technology-intensive environments in which nurses perform safety-critical roles. This review aimed to reframe workplace safety, wellbeing, and performance among operating room nurses as interconnected system-level determinants of perioperative care. Using a thematic narrative approach and conceptual scope, literature published mainly between 2020 and 2026 was reviewed, with selected foundational studies included where conceptually necessary. Evidence was synthesized across occupational hazards, psychosocial stress, emotional labor, burnout, compassion fatigue, quality of work life, teamwork, safety culture, distractions, cognitive load, ergonomics, robotic surgery, artificial intelligence, perioperative competency, empowerment, retention, and workforce sustainability. The findings indicate that unsafe or poorly supported operating room environments expose nurses to physical, psychological, cognitive, ergonomic, and technological pressures that may compromise wellbeing and professional performance. Nurse wellbeing supports attention, communication, emotional regulation, resilience, clinical judgment, and participation in safety practices. Conversely, burnout, compassion fatigue, interruptions, hierarchical communication, ergonomic strain, and inadequate technology readiness may weaken vigilance, teamwork, procedural reliability, and patient-safety margins. Operating room nursing performance is therefore multidimensional, encompassing technical competence, infection-prevention behavior, situational awareness, adaptability, speaking-up behavior, and technology-enabled workflow coordination. Treating nurse safety and wellbeing as patient-safety and system-performance priorities may strengthen surgical care, teamwork, retention, and the sustainability of perioperative healthcare systems.